PEG-like nanoprobes: multimodal, pharmacokinetically and optically tunable nanomaterials. - Yanyan Guo (PLoS ONE, 2014)
"PEG-like Nanoprobes" (PN's) are pharmacokinetically and optically tunable nanomaterials whose disposition in biological systems can be determined by fluorescence or radioactivity. PN's feature a unique design where a single PEG polymer surrounds a short fluorochrome and radiometal bearing peptide, and endows the resulting nanoprobe with pharmacokinetic control (based on molecular weight of the PEG selected) and optical tunability (based on the fluorochrome selected), while the chelate provides a radiolabeling option. PN's were used to image brain capillary angiography (intravital 2-photon microscopy), tumor capillary permeability (intravital fluorescent microscopy), and the tumor enhanced permeability and retention (EPR) effect (111In-PN and SPECT). Clinical applications of PN's include use as long blood half-life fluorochromes for intraoperative angiography, for measurements of capillary permeability in breast cancer lesions, and to image EPR by SPECT, for stratifying patient candidates for long-circulating nanomedicines that may utilize the EPR mechanism.